312 MALARIA EDUCATION IN GHANA. (1st January 2006) - Flynn, J.
Abstract : Purpose: Kumasi, Ghana has an extraordinarily high number of cases of severe malaria. A community project was designed to supplement the current Ghanaian public health projects aimed at teaching people how to avoid malaria infection and how to handle a suspected case of malaria. Methods: The first task was to educate teenage girls on the dangers of malaria. The second task was to educate current Ghana Red Cross Youth Educators on the topic of malaria prevention and first aid so that they can do talks on malaria. The third and final task was to develop a culturally appropriate reference guide on the topic of malaria. Results: Twenty youth educators were trained to give talks on malaria. Ninety teenage girls were supplied with the same information, and a guide to giving such talks was written and submitted to the Ghana Red Cross Society for possible nationwide use. Conclusions: Malaria education in Ghana is an ongoing and overwhelming struggle that frustrates many health professionals. Malaria itself is an omnipresent and overwhelming disease that destroys lives. A large hurdle in malaria education is finding a way to teach people who struggle with illiteracy and poor education how they can fight something they do not understand. Teaching youth educators about malaria is one step towards making complicated microbiology accessible to people who do not even know how to read. Providing those youth educators with a reference guide that puts scientific information into terms that they can understand is another step.